Association between timing of intubation and mortality in patients with idiopathic pulmonary fibrosis - Eunhye Bae; Jimyung Park; Sun Mi Choi; Jinwoo Lee; Sang-Min Lee; Hong Yeul Lee (Acute and Critical Care, 2022)
Background Delayed intubation is associated with poor prognosis in patients with respiratory failure. However, the effect of delayed intubation in patients with idiopathic pulmonary fibrosis (IPF) remains unknown. This study aimed to analyze whether timing of intubation after high-concentration oxygen therapy was associated with worse clinical outcomes in IPF patients. Methods This retrospective propensity score-matched study enrolled adult patients with IPF who underwent mechanical ventilation between January 2011 and July 2021. Patients were divided into early and delayed intubation groups. Delayed intubation was defined as use of high-concentration oxygen therapy for at least 48 hours before tracheal intubation. The primary outcome was intensive care unit (ICU) mortality, and a conditional logistic regression model was used to evaluate the association between timing of intubation and clinical outcomes. Results The median duration of high-concentration oxygen therapy before intubation was 0.5 days in the early intubation group (n=60) and 5.1 days in the delayed intubation group (n=36). The ICU mortality rate was 56.7% and 75% in the early and delayed intubation groups, respectively, before propensity matching (P=0.075). After matching for demographic and clinical covariates, 33 matched pairs were selected. In the propensity-matched cohort, delayed intubation significantly increased the risk of ICU mortality (adjusted odds ratio, 3.99; 95% confidence interval, 1.02–15.63; P=0.046). However, in-hospital mortality did not differ significantly between the groups. Conclusions In patients with IPF, delayed intubation after initiation of high-concentration oxygen therapy was significantly associated with increased risk of ICU mortality compared to early intubation.